Analisis Keseimbangan Beban dan Harmonisa Di Gedung Graha Polinema - Ahmad Hermawan; Mudjiono; Chandra Wiharya; Siffa Seftiana (Elposys: Jurnal Sistem Kelistrikan, 2021)
A large load imbalance is caused by the use of single-phase loads in a three-phase system, and poor harmonics are caused by non-sinusoidal loads, which result in losses in the network and poor quality of power distribution. This study aims to monitor and analyze load balance and harmonics in the Graha Polinema Building at Politeknik Negeri Malang. The research is a survey and case study using primary data obtained through direct measurement using a Web-Based Power Quality Meter (PM 5110) to gather data from each SDP panel, and secondary data through observation. From this study, the highest current imbalance value of 133.50% was found in the North 4th Floor SDP Panel of the Grapol Building, exceeding the IEEE 1159-2009 standard, which sets the limit for load imbalance at 30%. Current Harmonic Distortion (IHD) occurred in 8 SDP panels, except for the North and South Water Pump Panels. Total Demand Distortion (TDD) for all panels was within the standard limits. Total Harmonic Distortion (THDv) for all panels was also within the standard limits, with the highest value of 2.37% found in the North 4th Floor Panel.